2021
DOI: 10.1021/acs.jafc.1c00237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Soluble Dietary Fibers during the In Vitro Fermentation Process

Abstract: Soluble dietary fibers being fermented by gut microbiota constitute a pivotal prerequisite for soluble dietary fibers exhibiting physiological functions. However, the relationship between fiber type and gut microbiota metabolism remains unclear. The purpose of this study was to investigate and compare the effect of fiber types on short-chain fatty acid (SCFA) biosynthesis in a simulated colon. Results showed that different soluble dietary fibers caused distinct metabolic profiles both in SCFAs and organic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Bifidobacterium adolescentis and Ruminococcus bromii have shown the ability to use resistant starch [52], and the microbial community that degrades the type 3 resistant starch was also composed of highly amylolytic microbes (Prevotella, Bacteroides, and Lactobacillus) [53]. In this study, the relative abundance of Bacteroides and Parabacteroides increased after PRS treatment, which is consistent with a previous report [54]. Parabacteroides, belonging to Bacteroidetes, is a saccharolytic anaerobe that produces acetate, butyrate, and succinate as end products of carbohydrate fermentation [38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bifidobacterium adolescentis and Ruminococcus bromii have shown the ability to use resistant starch [52], and the microbial community that degrades the type 3 resistant starch was also composed of highly amylolytic microbes (Prevotella, Bacteroides, and Lactobacillus) [53]. In this study, the relative abundance of Bacteroides and Parabacteroides increased after PRS treatment, which is consistent with a previous report [54]. Parabacteroides, belonging to Bacteroidetes, is a saccharolytic anaerobe that produces acetate, butyrate, and succinate as end products of carbohydrate fermentation [38].…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of fecal SCFAs in KON and PRS was higher than that in LIG, which can be explained by the different ratios of soluble fiber/insoluble fiber between KON, PRS, and LIG, because LIG contains higher levels of insoluble fiber cellulose [18]. There was no difference in the SCFAs production between PRS and KON, and the total SCFA of KON was numerically higher, which is consistent with a previous report [54]. Conversely, the defecation frequency and serum gut motility regulator in PRS are higher than that in KON.…”
Section: Discussionsupporting
confidence: 90%
“…The advantage of the in vitro model is that most of the disturbances from the complex environment are eliminated. In our research, we found that LPs markedly decreased the microbial diversity, probably because insufficient carbohydrates in the fermentation system inhibited the growth of gut microbiota [31]. It is commonly believed that obese individuals exhibit a high ratio of Firmicutes to Bacteroidetes [32].…”
Section: Discussionmentioning
confidence: 57%
“…Boulaka [ 42 ] explored the metabolic markers of edible mushrooms containing β-glucan associated with healthy aging in humans and found significant increases in short-chain fatty acids (acetate, propionate, and butyrate), phenylalanine and tyrosine, trimethylamine, and γ-aminobutyric acid (GABA). Bai [ 43 ] found that KEGG pathways associated with soluble dietary fiber metabolism and SCFA synthesis include pyruvate metabolism and glycolytic and dicarboxylic acid metabolism. Whereas the effects of different DFCs on metabolites after in vitro fermentation in longevity dietary patterns are less reported, the present study found that different DFCs play a probiotic role in different metabolic pathways in the intestine by producing different metabolites from metabolomics.…”
Section: Discussionmentioning
confidence: 99%